Enhancing CBT for Chronic Insomnia: A Randomised Clinical Trial of Additive Components of Mindfulness or Cognitive Therapy. (5th October 2016) - Wong, Mei Yin; Ree, Melissa J.; Lee, Christopher W.
Abstract : Although cognitive behavioural therapy (CBT) for insomnia has resulted in significant reductions in symptoms, most patients are not classified as good sleepers after treatment. The present study investigated whether additional sessions of cognitive therapy (CT) or mindfulness‐based therapy (MBT) could enhance CBT in 64 participants with primary insomnia. All participants were given four sessions of standard CBT as previous research had identified this number of sessions as an optimal balance between therapist guidance and patient independence. Participants were then allocated to further active treatment (four sessions of CT or MBT) or a no further treatment control. The additional treatments resulted in significant improvements beyond CBT on self‐report and objective measures of sleep and were well tolerated as evidenced by no dropouts from either treatment. The effect sizes for each of these additional treatments were large and clinically significant. The mean scores on the primary outcome measure, the Insomnia Severity Index, were 5.74 for CT and 6.69 for MBT, which are within the good‐sleeper range. Treatment effects were maintained at follow‐up. There were no significant differences between CT and MBT on any outcome measure. These results provide encouraging data on how to enhance CBT for treatment of insomnia. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Message: CBT treatments for insomnia can be enhanced using recent developments in cognitive therapy. CBT treatments for insomnia can be enhanced using mindfulness‐based treatments. Both cognitive therapy and mindfulness produce additional clinically significant change.